Tailoring the Mutual Gains Approach for Negotiations with Partners in Japan, China, and Korea - Movius, Hal; Matsuura, Masa; Yan, Jin; Kim, Dong-Young (NEGOTIATION JOURNAL, 2006)
An increasing number of Western firms are negotiating agreements with business partners in Asia and must achieve business-critical results while building and protecting relationships. In this article, we review the literature regarding negotiation norms and approaches in Japan, China, and Korea. Drawing on structured interviews with experienced business executives at Hewlett-Packard, a U.S. corporation with a substantial presence in these countries, we highlight ways in which cross-cultural difficulties can arise in negotiations between American organizations and their Eastern counterparts. We note similarities and differences across these cultures and propose an expanded prescriptive model on how to adapt and implement a mutual gains approach to negotiation with counterparts who are based in Japan, China, and Korea.
Keywords: mutual gains approach; cross-cultural negotiation; business partnerships; Japan; China; Korea; Hewlett–Packard